2014
DOI: 10.1002/jbm.b.33254
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical properties, SEM, and EDS microanalysis of dentin treated with 2.5% titanium tetrafluoride, before and after an erosive challenge

Abstract: The aim was to assess the nanohardness (H) and the reduced modulus of elasticity (Er ) of 2.5% titanium tetrafluoride (TiF4 ) modified dentin, before and after an erosive challenge with 0.3% citric acid (CA). Exposed dentin surfaces were divided into two groups (n = 5): (1) Control-no dentin pretreatment with TiF4 prior to etching with CA, and (2) Experimental-dentin pretreatment with TiF4  + CA. The H and the Er of intertubular dentin were measured using a triboindenter at different time points: baseline for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 35 publications
0
34
0
3
Order By: Relevance
“…The matrix, even though suggested to be removed prior to laboratorial analysis (17), may have been important to inhibit the progression of erosive lesions, especially when treated with TiF 4 . Some authors reported that TiF 4 produces a glaze on the dentin surface (6,18) and one of the strongest actual theories to explain this formation considers the direct interaction between titanium and the organic matrix (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The matrix, even though suggested to be removed prior to laboratorial analysis (17), may have been important to inhibit the progression of erosive lesions, especially when treated with TiF 4 . Some authors reported that TiF 4 produces a glaze on the dentin surface (6,18) and one of the strongest actual theories to explain this formation considers the direct interaction between titanium and the organic matrix (8).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, fluoride compounds of polyvalent metal ions, especially titanium tetrafluoride (TiF 4 ), have been studied due to their unique interaction with the tooth structure, leading to the formation of an acid-resistant glaze-like layer capable of adhering strongly to the tooth surface (6). Among the existing theories to explain its action, one is that titanium is capable of reacting with the oxygen atoms of the phosphate groups of the dental tissue, forming stable titanium oxides (7) or organometallic complexes that can act as a diffusion barrier (8).…”
Section: Introductionmentioning
confidence: 99%
“…There is a plethora of models in the literature [Ganss et al, 2001[Ganss et al, , 2010[Ganss et al, , 2014Schlueter et al, 2007;Wiegand et al, 2008Hara et al, 2013;Borges et al, 2014;Basting et al, 2015], with variations in the number of cycles, incubation periods, and days of treatment. Our chosen protocol of 6 daily cycles of de-remineralization for 5 days showed the most significant difference between our negative (no treatment) and positive (AmF/NaF/ SnCl 2 ) controls.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, prolonged application times, between 2 and 4 minutes, may favor the retention of F -on the dental surface 35 and decrease mineral loss by dental tissue under acid action 19 . The ideal clinical application frequency has not still been determined, but it is known that TiF 4 is capable of modifying surface morphology since its first application 43 , leading to the formation of a smoother surface 49 and covered by precipitate both in enamel 38 and in dentin 50 . However, re-application of the fluoride may favor the reduction of substrate loss after tissue exposure to erosive solutions 43 and to promote certain obliteration of tubule entrance 49 , which could also lead to reduction of dentin hypersensitivity.…”
Section: Titanium Tetrafluoridementioning
confidence: 99%